Fatal cases associated with eating chapatti contaminated with organophosphate in Tororo District, Eastern Uganda, 2015: case series - Kwesiga, Benon (BMC Public Health, 2019)
BACKGROUND: Few cases of organophosphate poisoning in developing countries have been investigated using clinical and epidemiological methods. On 30 October 2015, 3 students at Mukuju School, Tororo District, Uganda, died soon after eating chapatti (locally-made flat bread) from the same food stand. Ministry of Health investigated to identify the cause and recommend prevention measures. METHODS: We defined a case as onset during 30–31 October 2015 in a resident of Mukuju Town of ≥1 of the following symptoms: excessive saliva, profuse sweating, dizziness, low blood pressure, constricted pupils or loss of consciousness. We reviewed medical/police records and interviewed survivors, healthcare workers, and police officers. We collected samples of implicated food for toxicological analysis. Autopsies were performed on decedents to identify the cause of death. RESULTS: We identified 7 cases with 3 deaths (case-fatality ratio = 43%). Clinical manifestations included acute onset of confusion (100%), constricted pupils (43%), excessive saliva (43%), and low blood pressure (43%). All 7 cases had onset from 16:00–18:00 h on 30 October, with a point-source exposure pattern. Of the 7 cases, 86% (6/7) were men; the mean age was 24 (range: 20–32) years. The 3 decedents each ate a whole chapatti while the other 4 cases ate half or less. Autopsy findings of the 3 decedents indicated organophosphate poisoning. Toxicological analysis found high levels of malathion in leftover foods (266 mg/L in dough and 258 mg/L in chapatti) and malaoxon (a highly toxic malathion derivative) in decedents’ postmortem specimens (mean levels of 19 mg/L in the blood and 22 mg/L in the gastric contents). There was a delay of 4 h before the patients received appropriate treatment. Police investigations revealed that flour used to make the chapatti was intentionally contaminated with an organophosphate pesticide. CONCLUSION: This fatal outbreak of organophosphate poisoning was associated with consumption of roadside-vended chapatti made of flour contaminated with pesticide. Clinicians should be aware of symptoms of organophosphate poisoning and prepared to treat it quickly. Street vendors should carefully consider the source of their ingredients. An in-depth surveillance review of such poisonings in Uganda would guide policymakers in reducing access by criminals and accidental exposures for the public. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12889-019-7143-0) contains supplementary material, which is available to authorized users.